Normative Fitness in Undergraduate Exercise Science Students: How Do They Compare?. Issue 1 (2nd January 2022) - Barton, Andrea; Zabriskie, Hannah A.; Moxley, Jennifer; Blackshear, Tara
ABSTRACT: The purpose of this study was to report normative physical fitness data for Exercise Science undergraduate students and compare the findings with criteria published by the American College of Sports Medicine (ACSM). 514 participants (males, n = 204; females, n = 310) aged from 18 to 29 years participated in this descriptive study. Pre-exercise heart rate and blood pressure, body mass index, waist circumference, skinfold thicknesses to estimate total body fat percentage (BF%), estimated maximal oxygen intake (VO2max ), and muscular endurance were evaluated. Percentiles were calculated and compared to those from the ACSM, with hypothesis testing of the medians. The median BF% for male students was leaner ( p < 0.001) than criterion standards. VO2max was lower compared to the published median in both sexes ( p < 0.001). Students performed on par with ACSM-published muscular endurance assessments. Exercise Science students are not fitter than the normative data published by the ACSM.